The effect of deep venous thrombosis on oxidative damage and vitamin A and beta-carotene levels - Turker, Fevzı Sarper; Doğan, Ayşe; Erisir, Mine (My University, 2020)
Objectives: This study aims to investigate the effect of deep venous thrombosis (DVT) on oxidative damage, vitamin A, and beta-carotenelevels.Patients and methods: A total of 50 DVT patients (29 females, 21 males; mean age 48 years; range, 20 to 75 years) who were admittedto the cardiovascular surgery clinic of Elazığ Training and Research Hospital with acute (<2 weeks) or chronic (?4 weeks) DVT and 100healthy individuals (54 females, 46 males; mean age 46 years; range, 16 to 69 years) between January 2018 and July 2018 were included.Malondialdehyde, vitamin A, and beta-carotene levels in plasma of peripheral blood samples were analyzed.Results: Demographic characteristics of the acute and chronic DVT patients were similar (p>0.05). In all DVT patients having thrombosisin the distal and proximal leg veins, the mean malondialdehyde (MDA) levels significantly increased and the mean levels of vitamin Asignificantly decreased, compared to healthy controls (p<0.05). No significant difference was found in vitamin A levels and demographiccharacteristics between acute and chronic DVT patients (p>0.05).Conclusion: Our study results suggest that decreased vitamin A levels may play a role in the development of DVT.
Keywords: Periferik Damar Hastalıkları; Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp